Short-Run Dynamics Between Income Inequality and Market Capitalisation-to-GDP in Indonesia - Dananjaya, Gde Putra; Chaidir, Taufiq (Syntax Corporation, 2026)
Using annual time-series data from 1998 to 2024, this research examines the short-run connection between income inequality and capital market size in Indonesia. Capital market size is indicated by the market capitalisation-to-GDP ratio (Buffett Indicator), and income inequality is measured with the Gini ratio. The Ordinary Least Squares (OLS) is used as the main regression method, and the model estimation focuses on short-run dynamics. Control variables that are included in the estimation are GDP per capita and inflation. By using the Augmented Dickey–Fuller (ADF) test, it can be confirmed that the transformed variables are stationary. The OLS shows that deviations in wealth distributions do not have a statistically significant association with changes in the market capitalisation to GDP ratio in Indonesia. The control variables are also found to be statistically insignificant in explaining short-run dynamics in Indonesian capital market development. Diagnostic tests such as Breusch–Godfrey LM and White and Jarque–Bera reveal that all data have no correlation problem and are free from heteroscedasticity. Moreover, consistency is provided through a robustness check with lagged inequality changes. To sum up, our results suggest that the changes in Indonesia's market capitalisation-to-GDP ratio in the short run may be more likely affected by factors other than changes in wealth distribution.